A coordinated mechanism for multimode user equipment accessing wireless sensor network. (1st January 2014) - Xia, Jun; Yun, Rui; Yu, Kai; Yin, Fei; Wang, Haifeng; Bu, Zhiyong
User Equipment (UE) as a basic device in cellular networks may contain different types of sensor module for specified usage, called multimode UE. With the natural mobility characteristics, this new type of UE is similar to an enhanced type of mobile sensor, with more energy and more flexibility. Since Wireless Sensor Network (WSN) can be deployed easily as no major infrastructure and human control are needed, the integration of cellular network and wireless sensor network becomes attractive by combining the sensing part and the connection part in a flexible way, which expands both scalability and service applications for the networks. In this paper, we propose a coordinated accessing mechanism when UE interacts with WSN network. Through the analysis of the accessing problem, we can optimise the contention period for accessing in order to enhance the heterogeneous network performance. The simulation result shows the proposed accessing mechanism outperforms the conventional method in an integrated network.